IgG4-related Kidney Disease Mimicking Malignant Ureter Tumor: Case Report and Literature Review. Issue 3 (January 2016) - Lei, Wen-hui; Xin, Jun; Shao, Chu-xiao; Mao, Ming-feng; Zhu, Chao-yong; Wu, Chui-fen; Jin, Lie
Abstract : Abstract: Immunoglobulin G4-related disease is a recently recognized systemic disease that can affect any organ or tissue in the body, including the kidneys. IgG4-related kidney disease (IgG4-RKD) is an important part of immunoglobulin G4-related disease. The most common renal manifestation of IgG4-RKD is tubulointerstitial nephritis and glomerular lesions. There, however, is few case of IgG4-RKD mimicking malignant ureter tumor leading to severe hydronephrosis. We herein report an unusual case of IgG4-RKD mimicking malignancy. A 66-year-old Asian man presented to the nephrologist with soreness of loins, anorexia, and acute kidney injury in 2010. His renal function spontaneously improved after 2 weeks' hemodialysis without systemic steroid therapy. Four years later, he presented to the urologist with severe left hydronephrosis because of marked thickness of the left ureter wall. As a ureteral malignancy could not be ruled out, laparoscopic nephroureterectomy was performed.IgG4-related kidney disease was confirmed by the histologic examination. Then, repeat laboratory test showed almost complete recovery of renal function after initiation of steroidal therapy. This case highlights the rare possibility of IgG4-RKD mimicking malignant ureter tumor. Nephrologist and pathologists should be aware of the possibility that hydronephrosis with ureter obstruction may be involved in IgG4-RKD.